PEMBELAJARAN PENGURANGAN PECAHAN MELALUI PENDEKATAN REALISTIK DI KELAS V SEKOLAH DASAR - Martianty Nalole (Jurnal Inovasi, 2008)
Study of reduction through approach of realistic is approach of study designed to give opportunity to student to find again (reinvention) mathematics concept without adult tuition (teacher) but relied on knowlwdge which have been owned by this student. Study give opportunity to student to find by self conception mathematics by finishing various problem of kontekstual.